2022
DOI: 10.1177/08862605211072167
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and Culturally-Specific Factors Related to Intimate Partner Violence Victimization among a Sample of Latino Sexual Minority Cis Men in the U.S.

Abstract: A growing body of research illustrates that sexual minority men (SMM) experience elevated rates of intimate partner violence (IPV) compared to heterosexual individuals. Researchers have examined the relationship between minority stress and IPV victimization among sexual minority men. A majority of the IPV research identifying risk factors associated with IPV victimization among SMM have sampled predominately non-Hispanic White SMM, while Latino SMM are consistently under-represented in IPV research. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…However, even though the scale measures a crucial aspect of discrimination, it does not cover all the factors that may lead to discrimination based on sexual orientation. Studies have linked IPV experiences to race-related discrimination but not sexual orientation-identity-discrimination ( 34 ). Specifically, Robles et al ( 34 ) found that race-based discrimination increased the odds of IPV victimization in Latino sexual minority men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even though the scale measures a crucial aspect of discrimination, it does not cover all the factors that may lead to discrimination based on sexual orientation. Studies have linked IPV experiences to race-related discrimination but not sexual orientation-identity-discrimination ( 34 ). Specifically, Robles et al ( 34 ) found that race-based discrimination increased the odds of IPV victimization in Latino sexual minority men.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have linked IPV experiences to race-related discrimination but not sexual orientation-identity-discrimination ( 34 ). Specifically, Robles et al ( 34 ) found that race-based discrimination increased the odds of IPV victimization in Latino sexual minority men. Thus, additional studies are needed to elucidate the potential role of specific forms of discrimination sexually minority men face to better predict their risk of IPV victimization.…”
Section: Discussionmentioning
confidence: 99%